2020
DOI: 10.1038/s41375-020-0742-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma DREAM Challenge reveals epigenetic regulator PHF19 as marker of aggressive disease

Abstract: While the past decade has seen meaningful improvements in clinical outcomes for multiple myeloma patients, a subset of patients does not benefit from current therapeutics for unclear reasons. Many gene expression-based models of risk have been developed, but each model uses a different combination of genes and often involves assaying many genes making them difficult to implement. We organized the Multiple Myeloma DREAM Challenge, a crowdsourced effort to develop models of rapid progression in newly diagnosed m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 35 publications
(31 reference statements)
4
48
0
Order By: Relevance
“…Therefore, PHF19 role in modulating MM biology has been a matter of investigation. Expression of PHF19 was reported as significantly associated with MM disease progression, showing a predictive value greater than NSD2 [ 47 ], an oncogene frequently over-expressed in MM plasma cells harboring the high-risk t(4;14) translocation; and reported to modulate by the oncogene NSD2 [ 48 ]. These findings prompted research groups to dissect the potential functional relevance of NSD2 -inhibition in MM.…”
Section: Epigenetics In Multiple Myeloma: Dna Methylation Histonementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PHF19 role in modulating MM biology has been a matter of investigation. Expression of PHF19 was reported as significantly associated with MM disease progression, showing a predictive value greater than NSD2 [ 47 ], an oncogene frequently over-expressed in MM plasma cells harboring the high-risk t(4;14) translocation; and reported to modulate by the oncogene NSD2 [ 48 ]. These findings prompted research groups to dissect the potential functional relevance of NSD2 -inhibition in MM.…”
Section: Epigenetics In Multiple Myeloma: Dna Methylation Histonementioning
confidence: 99%
“…To further define the oncogenic relevance of PHF19 in supporting MM biology, functional studies have been carried out and PHF19 -silencing approaches have demonstrated inhibition of MM cell cycle progression, reduction of MM cell proliferation and survival [ 47 ], thus recapitulating the importance for PHF19 in supporting MM pathogenesis and disease progression. Overall, targeting the PHF19-PRC2-EZH2 complex could represent a novel therapeutic strategy for MM treatment.…”
Section: Epigenetics In Multiple Myeloma: Dna Methylation Histonementioning
confidence: 99%
“…This has been demonstrated recently on multiple myeloma (MM), for which a histone methyltransferase, PHF19 , has been identified as the gene with the strongest association with myeloma progression. 78 This potential biomarker was also shown to exhibit greater predictive power than the well-known high-risk gene in MM, MMSET . The platform was also applied on other indications such as metastatic colorectal cancer 79 and Huntington’s disease, for which predictive models were generated based on data from clinical trials.…”
Section: Application Of Ai In Biomarker Discoverymentioning
confidence: 99%
“…Thus, the overexpression of the HMT PHD finger protein 19 (PHF19) and enhancer of zeste homolog 2 (EZH2) is a strong predictor of poor outcome. 99 , 103 EZH2 is a component of the polycomb repressive complex 2 (PRC2), which tri-methylates histone H3 lysine residue 27 (H3K27me3) to repress gene transcriptome related to stem cell self-renewal, cell cycle checkpoints, metastasis and cellular differentiation. Aberrant activity of EZH2 is regulated at multiple levels driven by interleukin-6 especially in cell lines that harbor K- and N-RAS mutations, 104 upregulation of NF-kB pathway 105 and downregulation of several microRNA (miRNA).…”
Section: Epigenomic Modificationsmentioning
confidence: 99%